2008
DOI: 10.2174/138955708786369564
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids: Prospective Drug Candidates

Abstract: The purpose of this review is to discuss the recent developments related to the chemistry and medicinal properties of flavonoids. Major flavonoids that show well categorized structures and well defined structure function-relationships are: flavans, flavanones, flavones, flavanonols, flavonols, catechins, anthocyanidins and isoflavone. The biological properties of flavonoids include antioxidant, anti-inflamatory, antitumoral, antiviral and antibacterial, as well as a direct cytoprotective effect on coronary and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
199
0
9

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(209 citation statements)
references
References 153 publications
1
199
0
9
Order By: Relevance
“…24) Sakuranetin, one of the flavonoids from I. viscosa, had been revealed to significantly increase insulinstimulated glucose uptake (1.5-fold at 100 mM in differentiated 3T3-L1 adipocytes), compared with control group. 15) In our study, the activity of 7-O-MA on 2-NBDG uptake was assessed in HepG2 cells and 3T3-L1 adipocytes by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…24) Sakuranetin, one of the flavonoids from I. viscosa, had been revealed to significantly increase insulinstimulated glucose uptake (1.5-fold at 100 mM in differentiated 3T3-L1 adipocytes), compared with control group. 15) In our study, the activity of 7-O-MA on 2-NBDG uptake was assessed in HepG2 cells and 3T3-L1 adipocytes by flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that phenolic phytochemicals exert anti-diabetic effect through inhibition of carbohydrate-hydrolyzing enzymes, such as alpha-amylase. In fact, many phenolic compounds and specially flavonoids have been reported as potential antidiabetic agents because they exert a good inhibitory action against α-amylase and could have potential prevention in diabetes mellitus as part of a dietary strategy [49]. These results were confirmed by others studies which showed that all of the tested Citrus flavonoids significantly inhibited amylase-catalyzed starch digestion [50].…”
Section: Inhibition Of α-Amylase Activitymentioning
confidence: 61%
“…These findings suggest that flavonoids have negligible systemic antioxidant activity, and that the increase in antioxidant capacity of blood seen after consumption of flavonoid-rich foods is not caused directly by flavonoids, but is due to production of uric acid resulting from flavonoid depolymerization and excretion 18 .…”
Section: Resultsmentioning
confidence: 90%
“…Flavonoids present in the all three extracts of this plant can also inhibit the activity of many enzymes such as xanthine oxidase, peroxidase and nitric oxide synthase, which are supposed to be involved in free radical generation, thereby resulting in decreased oxidative damage of macromolecules 18 .Research at the Linus Pauling Institute and the European Food Safety Authority shows that flavonoids are poorly absorbed in the human body (less than 5%), with most of what is absorbed being quickly metabolized and excreted. These findings suggest that flavonoids have negligible systemic antioxidant activity, and that the increase in antioxidant capacity of blood seen after consumption of flavonoid-rich foods is not caused directly by flavonoids, but is due to production of uric acid resulting from flavonoid depolymerization and excretion 18 .…”
Section: Resultsmentioning
confidence: 99%